Impact of cost of medicines for chronic conditions on low income households in Australia. (January 2013) - Kemp, Anna; Preen, David B; Glover, John; Semmens, James; Roughead, Elizabeth E
Objectives: To determine the cost of medicines for selected chronic illnesses and the proportion of discretionary income this would potentially displace for households with different pharmaceutical subsidy entitlements and incomes. Methods: We analysed household income and expenditure data for 9, 774 households participating in two Australian surveys in 2009-10. The amount of 'discretionary' income available to households after basic living and health care expenditure was modelled for households with high pharmaceutical subsidies: pensioner and non-pensioner concessional (social security entitlements); and households with general pharmaceutical subsidies and low, middle or high incomes. We calculated the proportion of discretionary income that would be needed for medicines if one household member had diabetes or acute coronary syndrome, or if one member also had two co-existing illnesses (gastro-oesophageal reflux disease and depression, or asthma and osteoarthritis). Results: Pensioner and low income households had little discretionary income after basic living and health care expenditure (AUD$92 and $164/week, respectively). Medicines for the specified illnesses ranged from $11-$42/month for high subsidy households and $34-$186/month for low subsidy households. Costs reduced substantially once patients reached the annual pharmaceutical cap (safety net), prior to which medicine costs would displace the equivalent of 1%-10% of discretionary income for most household types. However, low income households would have to forego the equivalent of between 5%-26% of their discretionary income for between 7 and 9 months of the year before receiving additional subsidies. Conclusions: Prescription medicines for chronic conditions pose a substantial financial burden to many households, particularly those with low incomes and general pharmaceutical subsidies. Policies are needed to minimize the cost burden of prescription medicines, particularly for low-income working households.